Gadolinium Changes the Local Electron Densities of Nickel 3d Orbitals for Efficient Electrocatalytic CO2 Reduction. (16th March 2022) - Liu, Weiqi; Bai, Peiyao; Wei, Shilin; Yang, Chuangchuang; Xu, Lang
Abstract: Generally, in terms of electrocatalytic CO2 reduction, single‐atom catalysts show high selectivities yet low current densities whereas conventional nanoparticle catalysts exhibit relatively high current densities but low selectivities. This work combines the advantages of the two classes of catalysts by constructing a Ni‐Gd‐N‐doped carbon black electrocatalyst within which Ni I active sites are exposed outside the carbon layers and Ni nanoparticles are encapsulated inside the carbon layers. The Gd atoms can not only influence the local electron densities of Ni 3d orbitals, thus strengthening the electronic activity, but also tailor the sizes of the Ni nanoparticles, thereby minimizing the activity toward hydrogen evolution. Accordingly, this electrocatalyst yields both a high CO faradaic efficiency (97 %) and a large current density (308 mA cm −2 ), alongside an outstanding stability (100 h). Abstract : Incorporation of Gd atoms into a Ni‐based catalyst readily changes local electron densities of the Ni 3d orbitals and strengthens the electronic activity. The resulting Ni‐Gd‐N‐doped carbon black electrocatalyst achieves high selectivity, large current density and outstanding stability in the electrocatalytic CO2 reduction.